PENGUASAAN TANAH MASYARAKAT HUKUM ADAT (SUATU KAJIAN TERHADAP MASYARAKAT HUKUM ADAT TERNATE) - Alting, Husen (Jurnal Dinamika Hukum, 2011)
Land acquisation by the community of adat law tends to leave out. This condition caused by the government policy before which has no attention to the development of land acquisition of the adat community. According that policy, all land are owned by the State, especially when its issue is about the government and bussiness interest. Reformation has changed the State system related to land acquisition, where the position of adat law community is diclared explicitly in the State constitution. The position of adat law community is agreed as long as not contradicted wiht public interest. The tale of seeking the existency of adat law community and the right of adat land acquisition shows that acquisition, mechanism and the area of adat law community still exist and have different characteristic between one and another. So that, State and the government should give protection and agreement to the right of adat law community as well as local wisdom as stated in its constitution. Key words: Land acquisation, right of adat community, adat law